Morphological And Morphometrical Studies Of Thymus In Non-Descript Puppies (Applied Biological Research, 2020)
Thymus is a primary lymphoid organ and well developed in young animals. Thymus is large and  most active during neonatal stage (Zdrojewicz et al., 2016). It is the modulator of activity of other  lymphoid organs, and the knowledge of mechanisms that triggers its development, maturation and  involution is vital for understanding the activity of whole lymphoid system (Sikora et al., 2002). The  information on the morphological studies on thymus gland in puppy is scanty; therefore, the present  study was conducted to record the morphological features during neonatal stage.
Keywords: Morphological; Morphometrical Studies; Non-Descript